The relationship between physical environment comfort and quality of worklife among supporting staff at Mahkamah Sesyen, Temerloh / Noor Fatma Muhamad - Muhamad, Noor Fatma (Faculty of Business and Management, 2018)
The purpose of this study is to examine the relationship between physical environment comfort and quality of work life among supporting staff at Mahkamah Sesyen, Temerloh. There were three independent variables used for present study namely air conditioning, noise and lighting. The dependent variable for this study was quality of work life. A set of 60 questionnaires were distributed among the supporting staff at Mahkamah Sesyen, Temerloh to achieve the objectives of this study. The data collected were analyzed by using SPSS program. Pearson Correlation was used as a measurement to investigate relationship between independent variable and dependent variable. The result found that two variables which was noise and lighting has significant relationship with quality of work life. However, air conditioning has no significant relationship with quality of work life. Lighting were the most influence towards quality of work life among supporting staff at Mahkamah Sesyen, Temerloh.